Sustainable mobility research: interdisciplinarity, conceptual articulation and research fronts - Pérez-Morales, Alfredo; Gil-Guirado, Salvador; Maqueda-Belmonte, Fernando (Documents d'Anàlisi Geogràfica, 2022)
Planning for sustainable mobility requires a holistic vision and an approach from different perspectives. It is necessary to know the research trajectories and fields of development that nourish this discipline, with its notable innovative character. In order to address this goal methodically, this paper develops a bibliometric analysis using a novel methodology. The results reveal that the fundamental concepts, methods and experiments revolving around sustainable mobility come from the social sciences, especially transport geography, urban planning, sociology and psychology. The predominant thematic areas identified were: strategic planning, the social component of transport, and new technologies. Among the main conclusions reached by the research under analysis was, notably, the fact that transforming the transport system into a sustainable model requires an increase in accessibility and a modal transformation.